Strategi Pemberdayaan Ekonomi dan Literasi Sosial Berbasis UMKM - Raisha Salsabila; Nabila Farah Dhiba; Angga Hade Fahrezi; Dea Ananda Pratama Hutabarat; Sriani Sriani (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The implementation of the Community Service Program (KKN) in Beringin Village was motivated by the community's low economic capacity, minimal social literacy, limited environmental management, and the need to strengthen religious values ​​amidst digital developments. These conditions demonstrate the importance of holistic and sustainable community empowerment-based interventions. This community service program used a qualitative descriptive method with a participatory approach, including observation, interviews, Focus Group Discussions (FGDs), mentoring MSMEs, biopore construction practices, and religious literacy development. The results of the activities showed an increase in MSME skills in digital marketing and financial recording, an increase in residents' ability to recognize hoaxes, the formation of more participatory social behavior, and growing environmental awareness through the implementation of biopores and organic waste management. In the religious field, mentoring in reading the Quran and mosque youth activities had an impact on increasing understanding and habituation of worship among the younger generation. Overall, this program made a significant contribution to strengthening the local economy, social resilience, environmental sustainability, and fostering community morality. These findings confirm that an empowerment approach based on collaboration and local needs is an effective strategy in realizing independent and sustainable village development